Immune checkpoint inhibitor use in antisynthetase syndrome. Issue 4 (27th February 2019) - Mackintosh, David; Islam, Mohammed F.; Ng, Jennifer; Basham, Jane
Abstract: We report on the unique case of a patient with antisynthetase syndrome and metastatic non–small cell lung cancer undergoing therapy with the PD‐1 checkpoint inhibitor, nivolumab. Despite adequate autoimmune disease control over a period of 12 months, the patient rapidly experienced a flare of interstitial lung disease following initial nivolumab administration, which ultimately proved fatal. The use of immune checkpoint inhibitors in patients with autoimmune disease is becoming more commonplace, however this is the first reported case of the use of these agents in a patient with antisynthetase syndrome. Additionally, the patient's initial clinical presentation with antisynthetase syndrome and simultaneous primary lung cancer, a rare association of which there are few case reports, makes this case interesting and unusual.